ACUTE LUNG INJURY: ISSUES AND REMAINING CHALLENGES (A LITERATURE REVIEW) - A. L. Rosstalnaya; D. M. Sabirov; R. N. Akalayev; V. K. Sharipova; M. L. Rosstalnaya; A. O. Mamirov (Неотложная медицинская помощь, 2016)
Basing on data of home and foreign literature, and own observations we discussed  modern views on the issue, and explained actuality of the further study of “acute lung injury” and “respiratory distress syndrome”. We considered the  questions of history, etiopathogenesis and diagnostic  criteria  of this pathological condition. Upon the discussion  of these  problems, we gave the particular  attention to the choice of an optimal artificial ventilation mode.